MICROBIOLOGICAL EVALUATIONS OF PERIODONTAL FILMS CONTAINING A COMBINATION OF PHARMACEUTICAL ACTIVE COMPOUNDS - K.S. Murlanova; V.P Shirobokov; I.V. Nizhenkovska; A.S. Voronkina; V.B. Nastenko; L.L. Davtian; N.O. Osypchuk (Bogomolets National Medical University, 2016)
Periodontal disease is the most common maxillofacial pathology. As a result of microbiology experiments there were selected optimal concentrations and combinations of active pharmaceutical ingredients; the spectrum of antimicrobial activity of experimental periodontal films was studied and compared with existing referent dental films. The most promising periodontal films for further research were selected (17 (Glu+Chl3+Met3), 15 (Chl3+Met3), 14 (Chl3+Met2) Ta 12 (Chl3+Met1)).